Skriveren og teksten - Straume, Ingerid S. (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"More and more people have to write in their jobs, and some need to write for publication. Students must learn to write in new genres, and their teachers not only need to write but also help others develop their own writing. Even though writing is often essential for learning a discipline and developing a professional identity, these aspects are often overlooked in academic settings. A surprising number of us struggle with writing, and often do so alone. Writing touches upon deeply personal processes concerning who we are in the eyes of others and how we view ourselves. This book elucidates the creative and subjective sides of professional and academic writing, which are in fact quite similar to those of literary writing. In the interview material, students and researchers share their experiences of the difficulties and the joys of writing, as well as personal decisions they have made in the course of becoming creative writers in their fields. In the discussion, a conceptual repertoire is developed from the philosophy of education, theories of identity development and recognition, to transcend the common belief that writing is something we either can or cannot master. The book will be of use to those who help others to write, and a source of inspiration for those who struggle with their own writing. The author is director of the Academic Writing Centre at the University of Oslo Library and editorial director of the website Søk & Skriv (Search & Write). She holds a doctoral degree in the philosophy of education and has many years' experience as a university lecturer, supervisor and professional academic writer."